Awe and the Experience of the Sublime: A Complex Relationship - Arcangeli, Margherita; Sperduti, Marco; Jacquot, Amélie; Piolino, Pascale; Dokic, Jérôme (Frontiers in Psychology, 2020)
Awe seems to be a complex emotion or emotional construct characterised by a mix of positive (contentment, happiness), and negative affective components (fear and a sense of being smaller, humbler or insignificant). It is striking that the elicitors of awe correspond closely to what philosophical aesthetics, and especially Burke and Kant, have called “the sublime”. As a matter of fact, awe is almost absent from the philosophical agenda, while there are very few studies on the experience of the sublime as such in the psychological literature. The aim of this paper is to throw light on the complex relationship between awe (as understood by psychologists) and the experience of the sublime (as discussed by philosophers). We distinguish seven ways of conceiving this relationship and highlight those that seem more promising to us. Once we have a clearer picture of how awe and the experience of the sublime are related, we can use it to enhance collaboration between these domains. We would be able to use empirical results about awe in a philosophical analysis of the experience of the sublime, which in turn can help us to design novel experimental hypotheses about the contexts in which we experience awe.